2013
DOI: 10.1093/humrep/det366
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-observer variability of time-lapse annotations

Abstract: NCT01139268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 19 publications
6
87
0
Order By: Relevance
“…However, the lack of information in this abstract regarding patient and sperm characteristics and cycle outcome prevents us from drawing any firm conclusion. Although annotating embryo development up to the blastocyst stage with TLM devices has been shown to be feasible with a fair reproducibility by trained operators [10], evaluating morula and the blastocyst stages remains a challenging issue. In order to minimize the operatordependent variation in blastocyst annotation, two trained embryologists performed this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lack of information in this abstract regarding patient and sperm characteristics and cycle outcome prevents us from drawing any firm conclusion. Although annotating embryo development up to the blastocyst stage with TLM devices has been shown to be feasible with a fair reproducibility by trained operators [10], evaluating morula and the blastocyst stages remains a challenging issue. In order to minimize the operatordependent variation in blastocyst annotation, two trained embryologists performed this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, morphokinetics has been shown to be more reproducible [10] and more accurate in predicting embryo quality and subsequent implantation than morphology alone [22], which suffers from limited performance. As the few other studies comparing embryo development according to sperm origin have been based on conventional morphology assessment, their conclusions should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported information on the association of the type of fertilization [22], the IVF protocol used [23], female obesity [24], and smoking [25] on embryo kinetics and development. Interestingly, the sensitivity and specificity of the modality in terms of predicting the progression to the blastocyst stage was >90 % by measuring parameters at day 2 after fertilization, before embryonic genome activation [26,27], while the bad prognosis of good-performing but unviable embryos reaches a specificity of 100 % [28]; moreover, the area under the receiver operating characteristic curve has been reported to be 0.74 for live birth [29] with high intra-and inter-observer correlation [30].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-observer variability evaluation demonstrated comparable results for most parameters. The authors indicated that embryo morphokinetic factors can be used certainly for embryo viability prediction, even the recording interpret by a trainee operator [54].…”
Section: Diferent Studies Based On Time-lapse Observationmentioning
confidence: 99%